Masterclass! understanding encryption - Rogers, Bobby; Safari eBooks ([S.l.] : Virtual Training Co., 2008)
"Protecting your confidential data, both on your computer and on the Internet, is of paramount importance in today's world. Encryption is the best measure you can take to protect your data from prying eyes, yet most people don't understand how it works or how they can use it to keep their data safe. VTC's resident computer security author Bobby Rogers will show you how encryption works - from the basics to advanced topics - why you need it, and how to make it work for you. To begin learning, simply click the links." --Resource description page.
Title from resource description page (viewed July 29, 2011).
Keywords: Data encryption (Computer science); Computers -- Access control; Computer security; Electronic books